LAMELLAR BODY COUNT WITH CELL DYN EMERALD AND CELL DYN RUBY METHODS ON PRETERM BIRTH - Widyastuti, Erlinda; Imandiri, Ario (Journal of Vocational Health Studies, 2017)
Background: Lamellar bodies are produced by pneumocyte type II cells in the lung alveoli. Lamellar bodies are present in amniotic fluid in increasing quantities as gestation advances, 1 – 5 µm in size, similar in size to small platelets and can be counted on most electronic cell counters in hematology analyzer. Lamellar body count is useful for prediction of fetal lung maturity and neonatal respiratory distress syndrome. The current gold standard for determination of fetal lung maturity is the evaluation of phospholipids in amniotic fluid samples by thin-layer chromatography, but it is time-consuming and not continuously available at most institutions. In this study we compare Cell Dyn Emerald and Cell Dyn Ruby method, which is expected to be a review for lamellar body count method. Purpose:  The aim of this study was to analyze lamellar body count with Cell Dyn Emerald and Cell Dyn Ruby method on preterm birth. Method: This was a cross sectional study. Thirty three samples study were inpatient's amniotic fluid with premature rupture of membranes in Obstetry and Gynecology ward emergency room Dr. Soetomo Hospital Surabaya. Lamellar body count was counted with Cell Dyn emerald and Cell Dyn Ruby method. The statistical differences were assessed using the ANOVA test . Result: The results showed significant differences (t=49,04), lamellar body count with Cell Dyn Ruby method was much lower than Cell  Dyn Emerald method. The lowest result with Cell Dyn Ruby method was 3.38 x 103/µL and 17 x 103/ µL with Cell Dyn Emerald method. The highest results with Cell Dyn Ruby method was 98,2 x 103/ µL and 221 x 103/ µL with Cell Dyn Emerald method. Conclusion: Lamellar body count with impedance method (Cell Dyn Emerald) is significantly higher than optic method (Cell Dyn Ruby).